FAKTOR RISIKO KEJADIAN STUNTING PADA BALITA USI 24-59 BULAN - admin, Nuraeni; Khairani, Masayu Dian; Abdullah; Dewi, Afiska Prima (Jurnal Gizi Aisyah, 2024)
Stunting makes you short as an adult and increases cases of obesity. The prevalence of stunting in Central Lampung District reached 20.4% and in the Simpang Agung Health Center (10.10%). This study aims to analyze the risk factors for stunting at the Simpang Agung Health Center in Central Lampung Regency in 2022. Observational study with a case control approach. The sample in this study was 86 children under five who were divided into two sample and control groups. Bivariate analysis in this study used the Chi Square Test. The results showed that a history of maternal CED during pregnancy (p value = 0.029, OR = 6.2) and birth length history (p value = 0.041, OR = 5.5) are risk factors for stunting in toddlers aged 24 -59 months while history of birth weight (p value = 0.24), history of exclusive breastfeeding (p value = 0.217, OR = 0.4), and history of immunization (p value = 0.483, OR = 2.2) not a risk factor for stunting in toddlers aged 24-59 months at the Simpang Agung Health Center. The conclusion of this study is that the mother's history of CED during pregnancy and birth length are risk factors for stunting, while birth weight, exclusive breastfeeding and immunization status are not risk factors for stunting.